Animal Models of Depression and Drug Delivery with Food as an Effective Dosing Method: Evidences from Studies with Celecoxib and Dicholine Succinate. (3rd May 2015) - Costa-Nunes, João P.; Cline, Brandon H.; Araújo-Correia, Margarida; Valença, Andreia; Markova, Natalyia; Dolgov, Oleg; Kubatiev, Aslan; Yeritsyan, Naira; Steinbusch, Harry W. M.; Strekalova, Tatyana
Abstract : Multiple models of human neuropsychiatric pathologies have been generated during the last decades which frequently use chronic dosing. Unfortunately, some drug administration methods may result in undesirable effects creating analysis confounds hampering model validity and preclinical assay outcomes. Here, automated analysis of floating behaviour, a sign of a depressive-like state, revealed that mice, subjected to a three-week intraperitoneal injection regimen, had increased floating. In order to probe an alternative dosing design that would preclude this effect, we studied the efficacy of a low dose of the antidepressant imipramine (7 mg/kg/day) delivered via food pellets. Antidepressant action for this treatment was found while no other behavioural effects were observed. We further investigated the potential efficacy of chronic dosing via food pellets by testing the antidepressant activity of new drug candidates, celecoxib (30 mg/kg/day) and dicholine succinate (50 mg/kg/day), against standard antidepressants, imipramine (7 mg/kg/day) and citalopram (15 mg/kg/day), utilizing the forced swim and tail suspension tests. Antidepressant effects of these compounds were found in both assays. Thus, chronic dosing via food pellets is efficacious in small rodents, even with a low drug dose design, and can prevail against potential confounds in translational research within depression models applicable to adverse chronic invasive pharmacotherapies.